BIOETHICS AGAINST DISAPPEARANCE OF A MAN A PRISM OF GENERAL AND CRIMINAL – LAW THEORY - Drakić, Dragiša; Trajković, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Bioethics, as a meeting point, engrossed with its fight against the disappearance of the man, both general and criminal-law theory. Actually, its ‘care’ for the man is an issue that comes before general and criminal-law theory. While the forms of disappearance of the man are very diverse and very often so refined that they cannon sometimes be recognized, the fight against the disappearance of the man must be open, clear and uncompromising. What is the role of law in this fight? The role imposed itself. Even if the law did not want to take part in the fight, it found itself in the middle of the battlefield because human life is protected from beginning to the end by legal norms that should emerge from the best writings of general and criminal-law theory. However, self-sufficiency of law and mere legal positivism are a true obstacle in this battle. This pressure and the lack of questionings are the first step on the road to disappearance of the man, because a man that asks questions is the man that exists. He and his boldness are a barrier to voluntarism. The lack of boldness of the man opens the gates to his disappearance. This boldness has not been taken away from him in the field of bioethics, which is neither secular nor religious, but rather unique as the man is unique.